Archiving Our Bodies: - Storm Madsen (Kvinder, Køn & Forskning)
This article analyses artworks by three non-binary or trans masculine artists: Kris Grey, No title (2019), Emmett Ramstad, The good ones (2006), and Marie Ahlberg Andersen, My Dick Clit has many forms (2022). I look at the corporeal traces the artworks display: wound scabs, blood drops, and crotch imprints, and find that they present a proof of trans becoming which, I would like to suggest, counters hegemonic narratives of transition and disturbs the notion of proof in relation to trans life; to highlight instead, the slowness, temporal multiplicity, and volatile uncapturability of trans embodiment. Through the article, I analyze Grey’s, Ramstad’s, and Andersen’s transition documentation as forms of counter-archiving, as well as how they function as t4t archival offerings – an invitation for other trans people to engage with their transition documentation and the potential of shaping their trans becoming through them. Through my personal narratives as refl exive, personal introductions to the analysis, the artworks, as a t4t archive, shed light on the moments and experiences that in small steps gets us, as trans people, closer to the way we want to be seen and feel about ourselves.